Coadsorption of CO and CH4 on the Au doped SnO2 (110) surface: a first principles investigation. (1st April 2022) - Chen, Ruixin; Yan, Longbin; Lin, Long; Deng, Chao; Zhang, Zhanying
Abstract: We researched the coadsorption of CO and CH4 molecule on the most stable structure of metal atom (Ni, Ag, Au, Rh, Zn, Pt) doped SnO2 (110) surface with the first principle methods. The formation energy results show that the Au/SnO2 (110) surface is the most stable structure. The adsorption energy, bond length, bond angle, density of states, electron population and charge density difference of gas molecule adsorbed on Au/SnO2 (110) surface are researched, which shows that Au/SnO2 (110) surface have excellent adsorption performance to CO and CH4 molecule. The stable adsorption of double CO on Au/SnO2 (110) surface shows that it has practical value. The research of CO and CH4 coadsorption on Au/SnO2 (110) surface shows that the Au/SnO2 (110) surface has stronger adsorption properties to CO than CH4 molecule. Our research indicates that Au/SnO2 is a potential CO sensor material.